DESIGN OF LIGHTWEIGHT CONCRETE WITH RECYCLED RUBBER AND ITS INFLUENCE ON THE PHYSICAL-MECHANICAL PROPERTIES IN MULTIFAMILY HOUSING - Támara Rodríguez, Joaquín Samuel; Chavarría Reyes, Liliana Janet; Reyes Roque, Reynaldo Melquiades; Barreto Palma, John Frayluis; De la Cruz Dueñas, Gustavo Gregorio; Deza Sanz, Alexander René; Durand Carrasco, Aldhair Anthony (LACCEI, 2025)
The present study focused on the development of a lightweight concrete modified with the incorporation of recycled rubber (RC), with the purpose of improving its physical and mechanical properties for its application in multifamily buildings. The problem addressed arises from the need for a material that combines low density, good workability and resistance suitable for use in multi-family housing, while promoting sustainability through the reuse of rubber waste. In this context, the general objective was to design a lightweight concrete that improves these properties, guaranteeing a balance between structural efficiency and environmental benefits.. lightweight concrete and the impact that the incorporation of recycled materials has on its physical and mechanical properties, in order to evaluate its viability in sustainable structural applications. The study used the deductive scientific method, applied orientation, quantitative approach, descriptive, explanatory, correlational and descriptive level. Experimental, longitudinal, prospective design and cohort study (cause – effect), where the proportions of CR in the concrete were varied. The results obtained indicate that the incorporation of CR improves the workability of the mixture, but reduces the unit weight by up to 35.99% and increases the settlement by 75.00% when 20% of CR is added. In addition, a decrease in the compressive strength of 12.93% and in the tensile strength of 26.67% is observed. The optimal dosage was determined at 5% CR, as it allows a balance to be achieved between better workability and a minimal reduction in strength, with a decrease of 5.6% compared to the control sample.